Salivary Biomarkers in Denture Stomatitis: A Systematic Review. (October 2019) - Khiyani, M.F.; Ahmadi, M.; Barbeau, J.; Feine, J.S.; de Souza, R.F.; Siqueira, W.L.; Emami, E.
Objective: Denture stomatitis (DS) is an oral biofilm–associated inflammation of the denture-bearing mucosa. The objective of this review was to identify and evaluate the quality of evidence on the association between the levels of salivary biomarkers and DS among adults with and without palatal DS. Materials and methods: Following the PRISMA guidelines, Medline, PubMed, EMBASE, and the Cochrane Central Register for Controlled Trials were searched for eligible studies from the beginning of the archives until December 2018. Experimental and observational studies with adult participants were included that had a control group or subgroup analysis and provided data on salivary biomarkers and DS. Articles in languages other than English or French were excluded. The level of evidence and grades of recommendation were established with the 2011 scale of the Oxford Centre for Evidence-Based Medicine. Additionally, the assessment of methodological quality was conducted with the STROBE statement (Strengthening the Reporting of Observational Studies in Epidemiology) and graded according to the Olmos scale. Results: From 1, 008 citations, 9 studies were included in the systematic review (8 observational, 1 clinical trial). Seven studies suggested a statistically significant difference in the levels of salivary cytokines (IL-6, CCL3, TGF-β, CXCL8, GM-CSF, and TNF-α) between participants with DS and controls ( P < 0.05). In contrast, 2 studies concluded that the difference in the levels of several salivary cytokines (IL2, IL12, IFN-g, IL-4, IL-8, IL-10, IL-17, TNF-α, and ICAM-1) between the groups was not statistically significant. The level of evidence for the majority of studies was 3, while the grade of recommendation for all the studies was B, interpreted as "favorable." In terms of methodological quality, most studies met 50% to 80% of STROBE criteria and were graded B. Conclusion: Palatal inflammation in DS is significantly associated with the levels of salivary cytokines. Knowledge Transfer Statement: The results of this study identified altered levels of specific salivary biomarkers associated with denture stomatitis, which may aid in the early diagnosis and treatment of this disease.